Strategic and relational factors affecting franchise performance: Systematic Literature Review (SLR) - Fazli Sofyand; Rehana Dwiba; Sudarmiatin; Trisetia Wijijayanti (Abadi Institute, 2026)
This study aims to analyze the various factors that affect the success of the relationship between franchisor and franchisee, as well as their impact on the performance and viability of the franchise network. The method used is the systematic literature review (SLR), where this study combines the results of various international studies that discuss things such as relationship quality, control mechanisms, information inequality, operational support, entrepreneurial attitudes, and organizational dynamics in the context of franchising. The findings show that the success of a franchise system is highly dependent on the level of trust, communication effectiveness, conformity in contractual expectations, and the ability of the network in balancing operational standards with local flexibility. Imbalance of control and lack of information transparency are the causes of conflicts that adversely affect franchisee satisfaction and loyalty. On the other hand, responsive franchisor support and collaborative relationships can improve network performance, loyalty and viability. This study emphasizes the importance of building flexible and mutually beneficial relationships in franchise management, and suggests further research on the digitization of relationships, franchisee organizational behavior, and strategies to strengthen the viability of the franchise system in the midst of increasingly fierce competition.